Estimating the prevalence of primary headache disorders in university students: Application of the Croatian version of the HARDSHIP questionnaire - Lukrecija Jakuš; Darija Mahović; Claire Alexandra Sangster Jokić; Matea Bračić; Ivan Jurak (SAGE Publishing, 2023)
Background: Studies reporting the prevalence of headaches in Croatia have methodological differences that make it difficult to consolidate their results. This study aimed to assess the prevalence of the most common primary headaches in a student population using the standardized HARDSHIP questionnaire (in Croatian). Methods: This cross-sectional epidemiological study collected data regarding the 1-year prevalence of headaches in a student population using the diagnostic algorithm of the HARDSHIP questionnaire. The chi-squared test was used to analyze gender differences, and Cramer's V was used for effect size interpretation. Results: The questionnaire was administered to 1350 university students enrolled in health profession programs (81.3% female; 18.7% male; average age: 23 years). The 1-year prevalence of migraine was 38.9% (male: female ratio, 1:1.5), and that of tension-type headache was 35.6% (male: female ratio, 1:0.9). Overall, 91.0% of participants responded positively to the question regarding the incidence of headache in the past 12 months. Conclusions: We report a high prevalence of primary headaches among students of health professions in Croatia. The differences in prevalence may be attributed to various sociocultural, geographical, genetic, and methodological differences. Population-specific studies may facilitate a more accurate assessment of headache prevalence and enable more effective targeting of public health activities.